To Exist is a Form of Resistance - Sarah Allen; Aina Landsverk Hagen (Journal of Extreme Anthropology)
Photography has long been associated with acts of resistance. In this interview, Sarah Allen, Head of Programme and co-curator of the exhibition Acts of Resistance: Photography, Feminisms and the Art of Protest at the South London Gallery, elaborates on the reasoning behind the show. The show includes works from 2012 to the present day, offering what The Guardian newspaper described as ‘a visual manifesto of the fourth wave of feminism’. The artworks illustrate how social media is influencing the creation and circulation of protest images and problematizes the photograph as ‘evidence’, thus breathing new life into the medium as an art form of protest. The selected artists are all moving beyond a documentary ‘style’ protest image towards work which embraces collage, the internet and performance. In the public programme of the exhibition, workshop participants were invited to conceptualise the interconnectedness of feminist struggles and how to organise across borders. Allen argues that public galleries play a vital role in platforming artists dealing with pressing social justice issues of the day.